Presidential Address: How Much “Rationality” Is There in Bond‐Market Risk Premiums? - SINGLETON, KENNETH J. (Journal of Finance, 2021)
ABSTRACT Beliefs of professional forecasters are benchmarked against those of a Bayesian econometrician who is learning about the unknown dynamics of the bond risk factors. Consistent with rational Bayesian learning, the forecast errors of individual professionals and are comparably predictable over the business cycle. The secular and cyclical patterns of professionals' forecasts relative to those of are explored in depth. Inconsistent with many models with belief dispersion, the relationship between professionals' yield disagreement and their matched disagreements about macroeconomic fundamentals is very weak.